Early Childhood Learning Mood Management through Video-Based Streamlining - Dakir Dakir; Hefniy Hefniy; Zubaidi Zubaidi; Faiqotul Himmah (AL-ISHLAH: Jurnal Pendidikan, 2022)
With the implementation of video-based learning at RA Masyitoh, this study aims to analyze and examine the management of learning mood in early childhood through video-based learning. The researcher employs the qualitative case study method.This study comprised interviews, observation, and documenting findings as data collection techniques. The data analysis is carried out in stages, beginning with data collection and progressing through data presentation, reduction, and conclusion. The results revealed that learning mood management in early childhood through video-based learning was accomplished through the following methods: needs analysis, implementation design of video-based learning, assessment of video-based learning. According to this research, students' learning mood must be maintained for optimization and learning targets to be achieved in the classroom. Teachers must do their part to ensure that this happens. Therefore, a comprehensive understanding is needed to improve children's learning mood through various learning approaches.